(untitled) (Research, Society and Development, 2020)
The objective of the work was to evaluate the characteristics of two biodegradable packaging from the residue of watermelon and incorporated with Sinningia elatior starch. The watermelon residue was collected on watermelon producing farms. The tuber of Sinningia elatior was collected in the municipality of Rio Verde, Goiás, Brazil. Biodegradable packaging was evaluated for thickness (mm), humidity (Tu%), ash (Tcz%), opacity, water solubility (%), swelling rate (%), pH, biodegradability, antioxidant activity for DPPH (%) and FRAP µMol g Fe+ 2, total phenolics expressed in mg GAE 100 g-1 DM, water vapor in g mm h-1 m-2 kPa, color, optical and scanning electron microscopy and 3D analysis. The following results were obtained for thickness 0.146 and 0.169 mm, humidity of 7.94 and 9.84%, ashes 0.04 and 0.82%, opacity of 3.089 and 1.147, solubility in water of 91.83 and 79.47%, swelling rate of 111.86 and 209.15%, pH of 6.25 and 7.14, biodegradability of 10 and 14 days, reduction of DPPH 74.28 and 81.89%, FRAP 126.68 and 155.49 µMol g Fe+ 2, total phenols of 3.61 and 15.20 mg EAG 100 g-1 MS, water vapor of 0.280 and 0.526 PVA g mm h-1 m-2 kPa, good color effects, homogeneity in microscopic and 3D analysis for double layer packaging and incorporated with S. elatior starch. Both biodegradable packaging presented in this study, important results in the development of two products based on residues and native starch.